Neurological Complications After Covid 19 Vaccinations: Serial Case Report - Intan Permata Sari; Hanindia Riani Prabaningtyas (Department of Neurology Faculty of Medicine Universitas Sebelas Maret, 2023)
Background: COVID-19 vaccination has been carried out worldwide, with more than 5 million dose of vaccine delivered. Although declared safe, there are cases of neurological disorders after the Covid 19 vaccination. Cases: In the first case, a 20-year-old male came with decrease level of consciousness, 4 days after receiving the first dose of COVID 19 vaccine with Sinovac vaccine. MRI Brain shows acute disseminated encephalomyelitis (ADEM). In the second case, a 50-year-old male with seizures and decreased consciousness after recieving first dose of COVID-19 vaccination with Sinovac vaccine, 10 days before admission. Non contrast CT Scan and brain contrast MRI Brain revealed cerebral edema. In the third case, an 18-year-old woman had seizures and decreased consciousness one month after the first dose of COVID 19 vaccination with Sinovac. Contrast Head MRI showing focal leptomeningitis. In the fourth case, a 30-year-old male with slurred speech and right-sided weakness. Three months before admission, he had fever, headache, and tingling of the right limbs a few days after the first dose of COVID 19 vaccination with Sinova MRI Brain Contrast shows ADEM lesion Discussion: The mechanism of neurological disorders concerning COVID 19 vaccination is still unclear. Neurological complications after vaccination weaken the effort of vaccination, but can be used as a precaution and assess prognosis while waiting for further confirmation from large epidemiological studies and meta-analyses. Until now, it is believed that the COVID-19 vaccine has important benefits and is a hope for ending the COVID-19 pandemic.